The Implementation of Good Governance Business Shariah in Indonesia Shariah Banking - Juanda, A; Dwi Herlyanto, F; Wahyu Oktavendi, T (KnE Social Sciences, 2019)
The aim of this research is to describe the implementation of Good Governance Business Shariah in Indonesia Shariah Banking. Content analysis is used in this study to identify GGBS indicators. Indicators in this research is formed from KKNG. The lowest percentage of implementation GGBS is Bank Mega Syariah. There’s 6 Shariah Banking that taking the leads of the GGBS implementation. The results show that the average implementation of GGBS in Indonesia Shariah Banking is 94%, this shows that shariah banking have implemented a good GGBS to maintain Indonesia Shariah Banking survibality and safeguard the interests of stakeholders. But several items may not disclosed in Shariah Banking Annual Report. Keywords: Good Governance Business Shariah, Content Analysis, Implemetation